Sistem Pendukung Keputusan Kelayakan Pemberian Asuransi Jiwa Untuk Nelayan dengan Menggunakan Metode Vikor (Studi Kasus: Dinas Kelautan dan Perikanan Medan) - Amatillah Nasution; Kurnia Ulfa (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Life insurance is a term used to refer to actions, systems, or businesses in which financial protection (or financial compensation) for life, property, health and so on gets reimbursed from unexpected events that can occur such as death , loss, damage or illness, which involves regular premium payments over a period of time in exchange for a policy that guarantees such protection. The term "insured" usually refers to everything that gets protection. Decision Support System is defined a system intended to support management decision making, Decision making is the main function of a manager or administrator. Decision making activities include identifying problems, finding alternative solutions to problems, evaluating these alternatives and choosing the best decision alternatives. The Vise Kriterijumska Optimazacija Kompromisno Resenje (VIKOR) method is one of the methods used in decision making. To use the decision support system method must have criteria that will be used in the determination, in addition it must determine the level of importance of each criterion. So the decision support system used must also have comprehensive and integrated planning to minimize the level of risk of failure and decision selection